Four new species of Sciodaphyllum (Araliaceae) from the Western Cordillera of the Andes in Colombia - Jiménez-Montoya, Jaider; Idárraga-Piedrahíta, Álvaro (Phytotaxa, 2025)
Four new species of Sciodaphyllum (Araliaceae) are described, each known only from a single locality in the northern part of the Western Cordillera of the Andes in Colombia. Sciodaphyllum apiciflorum, known from a foothill site close to Paramillo National Natural Park, is morphological similar to S. quindiuense and characterized by the two secondary axes of the inflorescence that are disposed at the apex of the primary axis, and the umbels that are arranged toward the apex of the secondary axes. Sciodaphyllum bracticonspicuum, known from the Murrí region, is morphological similar to S. blepharidophyllum but is characterized by the glabrescent and pale green stipular ligules and bracts that contrast with the tomentulose and dark axes, and the tomentose or floccose hypanthium. Sciodaphyllum monteblancense, from the Farallones of Citará mountain complex, is morphological similar to S. trianae but differs from this species mainly by the leaflets blades and corolla without scales abaxially, and the corolla internally tomentulose. Sciodaphyllum punctatum, from the border area between Antioquia and Risaralda departments, is morphological similar to S. manus-dei but characterized by the dense and tiny clusters of trichomes that look like dots uniformly distributed abaxially of the leaflet blades. Detailed descriptions, illustrations, and notes on the distribution, habitat, and taxonomy are provided for each species.